2018
DOI: 10.1103/physrevlett.121.064503
|View full text |Cite
|
Sign up to set email alerts
|

Transient Nonlinear Response of Dynamically Decoupled Ionic Conductors

Abstract: The present study demonstrates that large electric fields progressively enhance the conductivity of ionic systems up to timescales corresponding to those on which their structural rearrangements take place. Yet, in many ionic materials, some regarded as candidates for electrical energy storage applications, the structural relaxation process can be tremendously slower than (or highly decoupled from) the charge fluctuations. Consequently, nonlinear dielectric spectroscopy may be employed to access rheological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…In a lot of cases, when the polymer is soft, the ion interaction dominates the structural relaxation, as it is evidenced by rheology and dielectric research. ,,,,, The similar timescale correlations found for structural relaxation and conductivity relaxation indicate that the latter is also dominated by ion association–dissociation relaxations, stressing the same origin of both . Various degrees of decoupling of conductivity relaxation from structural relaxation are also possible when the polymer is less fragile. ,, Furthermore, ionic conductivity has also been found to be linearly scaled with ion-association time in a type of end-functionalized metal ion-containing polymer …”
Section: Resultsmentioning
confidence: 99%
“…In a lot of cases, when the polymer is soft, the ion interaction dominates the structural relaxation, as it is evidenced by rheology and dielectric research. ,,,,, The similar timescale correlations found for structural relaxation and conductivity relaxation indicate that the latter is also dominated by ion association–dissociation relaxations, stressing the same origin of both . Various degrees of decoupling of conductivity relaxation from structural relaxation are also possible when the polymer is less fragile. ,, Furthermore, ionic conductivity has also been found to be linearly scaled with ion-association time in a type of end-functionalized metal ion-containing polymer …”
Section: Resultsmentioning
confidence: 99%
“…15 Representing viscoelastic materials with dominating Coulombic interactions, type IV materials include an ionic liquid, 16 an ionic melt, 12 and two polymerized ionic liquids. 16,17 The former two electrolytes behave as "simple" liquids, the latter two display clear evidence of chain dynamics at frequencies below wa. The type V materials are linear polymers with different chain lengths, 18,19 whereas a water solution of lithium chloride 21 is considered as type VIcorresponding to aqueous systems.…”
mentioning
confidence: 99%
“…Fig. 1 Fluidity master curves constructed using the literature shear rheology data of various liquids including, as type I tris-naphthylbenzene (TNB) pentaphenyltrimethyltrisiloxane (DC704), dibutyl phthalate (DBP), diethyl phthalate (DEP), m-toluidine (mTOL), ortho-terphenyl (OTP), and propylene carbonate (PC), 12 as type II rhyolite, 13 as type III 3-methyl-3heptanol, 4-methyl-3-heptanol, 6-methyl-3-heptanol, 2-ethyl-1-hexaol, 2ethyl-1-butanol, 14 and H-bonded hydroxyl-terminated polydimethylsiloxane, 20 as type IV calcium nitrate-potassium nitrate (CKN), 12 N,N-Dimethyl-N-(2-(propionyloxy)-ethyl)butan-1-ammonium bis(trifluoromethanesulfonyl)imide, 16 10-mer and 109-mer of poly(Nvinylethylimidazolium) bis(trifluoromethylsulfonyl)imide, 16,17 as type V propylene glycol (PG) 12 and poly(propylene glycol) (PPG) with molecular weights of 5400 g/mol, 12200 g/mol, and 18200 g/mol, 18 as type VI a solution of 17 mol% LiCl in water, 21 and as type VII the metallic melt Zr50Cu40Al10. 22,23 The solid lines mimic the a response and is the same one (just shifted vertically) in cases I to VI, except case VII, see text for details.…”
mentioning
confidence: 99%
“…The latter was recently reported as a very suitable method to highlight multimodal behavior in the shear spectrum, and it was shown that the peak positions of η′′ are directly comparable to the ones from dielectric spectroscopy and thus also to those from DDLS. It is clear from Figure that the peak positions of both modulus representations ( G ″ and M ″) coincide as expected . At the low-frequency flank of G ″, a shoulder is discernible, not present in M ″.…”
mentioning
confidence: 99%